Voz humana sem amarras: abordagem a partir de Wolfsohn - Marambio, Denisse Elena Iturra (2013)
Alfred Wolfsohn (1896-1962), German researcher of human expression through voice. He participated as a soldier of the First World War, which caused a war neurosis: the starting point of formulating his ideas about the human voice, especially in relation to organic and functional conditions in association with emotional and affective dimensions of production and vocal preparation. Wolfsohn developed a detailed proposal preparation vocal for singers and actors, although it is still unfamiliar in Latin America, especially in Brazil. The aim of the dissertation was to describe some aspects related to Wolfsohn´s work, collaborating in the dissemination of his work and the debate about the possibilities of vocal preparation in Brazil. Additionally, as a specific objective, we discuss the design of vocal work of Wolfsohn, as well as a possibility of practical work it inspired. Our hypothesis was that, although there are similarities between the work of Wolfsohn and other preparers vocals, the novelty of the proposal of the German author regards the exploration of visceral vocal production, provided support plan preparation vocal. Concerning the methodology, this is an exploratory research, conducted through a literature review and systematic observation of a vocal preparation process, performed by the proposed of Wolfsohn. The results show that the research of Wolfsohn´s work has convergences with the literature of vocal preparation area, especially in the aspects related to the work with the breath, vocal support, posture, resonance, articulation and voice projection. Most authors raised in the literature review, refer psychological dimensions and / or psychological, which influence the vocal work, few directly address the practice in preparation for singing. Unlike, Wolfsohn seeks visceral voice from the Jungian notion of archetypes; tool that allows him contact with the unconscious and the drives, exploring the vocal range as privileged way for the expansion of human expression, which can be verified also systematic observation of the subjects of our research through the integration of perception and body / voice, which made to evolve in terms of linkage between perception of themselves and the world through the utterance. The conclusion points to the relevance of Wolfsohn´s proposal in the preparation of voice professionals, especially singers and may constitute as subsidy to speech therapy